PENGARUH PEMBERIAN EKSTRAK BIJI PEPAYA (Carica papaya Linn) TERHADAP KADAR LDL PADA TIKUS PUTIH JANTAN GALUR WISTAR (Rattus norvegicus) YANG DIINDUKSI DIET TINGGI LEMAK - ALZA HAMONANGAN PASARIBU; ILHAM HARIAJI (LP2MTBM MAKARIOZ, 2023)
Coronary Heart Disease (CHD) is one of the cardiovascular diseases that lead the causes of death and disability around the world. One of the risk factors that can cause CHD are hypercholesterolemia. Papaya seeds are one of an alternative plant that has a hypolipodemic effect. This research aim to know the effect of giving the papaya seeds extract (Carica Papaya Linn) in the LDL levels on male white rats Galur Wistar (Rattus Norvegicus) that induced with a high fat diet.This research is a true experiment with pretest – posttest design with a control group design. This research used a male white rats Galur Wistar (Rattus Norvegicus) that induced with a high fat diet, divided into four groups, which is a negative control group, positive control, the first way of treating (400 mg papaya seeds extract/head) and the second is (800 mg papaya seeds extract/head). The LDL levels were measured before and after the treat. The paired t test showed a significant decrease in the LDL levels with a doses of 400mg papaya seeds extract/head (p<0.001) and a dose of 800 mg papaya seeds extract/head (<0.001).There is a significant relationship between papaya seeds extract with the decrease in the LDL levels on white rats Galur Wistar.